2014
DOI: 10.2147/ndt.s64323
|View full text |Cite
|
Sign up to set email alerts
|

Risk of epilepsy in patients with systemic lupus erythematosus – a retrospective cohort study

Abstract: BackgroundSystemic lupus erythematosus (SLE) affects central and peripheral nervous systems, manifesting neuropsychiatric disorders that vary from subtle signs to life-threatening complications. This study compared the risk of epilepsy between a general population and patients with SLE.MethodsFrom the national insurance claims data of the Taiwan National Health Research Institutes, we identified 32,301 patients with newly diagnosed SLE from 1997–2010 and, for comparison, 129,204 randomly selected people withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
1
8
0
1
Order By: Relevance
“…Various reports indicated a high prevalence of seizures among people with SLE (prevalence:1.6%-16%) [3,8,[36][37][38][39][40][41]; and from studies including controls they seem higher than in the general population [8,[38][39][40][41]. A recent cross sectional study with over 5000 people with SLE and over 25,000 controls found epilepsy 4.7 times more likely in the SLE cohort (95% CI: 3.9-5.8%) [39].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
See 1 more Smart Citation
“…Various reports indicated a high prevalence of seizures among people with SLE (prevalence:1.6%-16%) [3,8,[36][37][38][39][40][41]; and from studies including controls they seem higher than in the general population [8,[38][39][40][41]. A recent cross sectional study with over 5000 people with SLE and over 25,000 controls found epilepsy 4.7 times more likely in the SLE cohort (95% CI: 3.9-5.8%) [39].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…Younger age, history of stroke, African descent, history of psychosis, history of malar rash, proteinuria, neuropathy and low levels of complement 3 (C3) seem associated with increased seizure risk [38,40,[42][43][44]. Seizures are more likely to happen in the year after the diagnosis of SLE [3,42] and are not explained by infection or antiphospholipid syndrome [3].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…Neuropsychiatric symptoms of SLE are associated with generalised SLE activity and often recur 11. The incidence of epilepsy in people with SLE is three times that of the general population and people with SLE and epilepsy are more likely to experience psychiatric disorders 12. However, as in this case, seizures often predate other symptoms by many years and so diagnosis of isolated epilepsy syndromes is common 13.…”
Section: Discussionmentioning
confidence: 96%
“…A study from Taiwan, retrospective in its design, contained 32,301 SLE patients matched with 129,204 controls, based on the national insurance claims data of the Taiwan National Health Research Institutes (1997–2010 as the study period) [35]. Authors found that the incidence of epilepsy was 2.86-fold higher in the SLE cohort than in the non-SLE cohort (9.10 per 10,000 person-years versus 3.18 per 10,000 person-years).…”
Section: Discussionmentioning
confidence: 99%